Relationship Between Paternalistic Leadership and Employee Innovation: A Meta-Analysis Among Chinese Samples - Lu, Lin; Zhou, Kaiji; Wang, Yingzhao; Zhu, Sishi (Frontiers in Psychology, 2022)
The meta-analysis was conducted to examine the relationships between three dimensions of paternalistic leadership and employee innovation in Chinese enterprises. There exists over a decade of empirical research on the influence of paternalistic leadership on employee innovation in China, but the findings from the various studies are not consistent. Sixty-nine studies from 2009 to 2021 were included in the meta-analysis, and 154 effect sizes were examined. The study found that two dimensions of paternalistic leadership (benevolent leadership r = 0.396 and moral leadership r = 0.329) were positively associated with employee innovation. In contrast, the dimension of authoritarian leadership was negatively associated with innovation (r = −0.151). Moderator analyses found that gender, the education level of employees, time, and the type of evaluation served as meaningful moderators. The moderating effects of outcome measure, the type of data collection method, and the type of publication were not significant. We discuss our limitations, implications for future studies, and practical implications for organizational management.